2019
DOI: 10.1111/oik.06353
|View full text |Cite
|
Sign up to set email alerts
|

Identifying important interaction modifications in ecological systems

Abstract: Trophic interaction modifications, where a consumer–resource link is affected by additional species, are widespread and significant causes of non‐trophic effects in ecological networks. The sheer number of potential interaction modifications in ecological systems poses a considerable challenge, making prioritisation for empirical study essential. Here, we introduce measures to quantify the topological relationship of individual interaction modifications relative to the underlying network. We use these, togethe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Empirical work demonstrates that these 'trophic interaction modifications' (Golubski & Abrams, 2011;Terry et al, 2017;Wootton, 1993) can drive population dynamics (Tack et al, 2011) and affect how communities respond to perturbation (Barbosa et al, 2017). Furthermore, theory suggests that the strength, direction and distribution of trophic interaction modifications within food webs influence community stability (Arditi et al, 2005;Terry et al, 2020) and ecosystem function (Goudard & Loreau, 2008). However, we know little about how trophic interaction modifications vary in strength and direction among many diverse potential modifier species in natural communities (Terry et al, 2020;Wootton & Emmerson, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical work demonstrates that these 'trophic interaction modifications' (Golubski & Abrams, 2011;Terry et al, 2017;Wootton, 1993) can drive population dynamics (Tack et al, 2011) and affect how communities respond to perturbation (Barbosa et al, 2017). Furthermore, theory suggests that the strength, direction and distribution of trophic interaction modifications within food webs influence community stability (Arditi et al, 2005;Terry et al, 2020) and ecosystem function (Goudard & Loreau, 2008). However, we know little about how trophic interaction modifications vary in strength and direction among many diverse potential modifier species in natural communities (Terry et al, 2020;Wootton & Emmerson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, theory suggests that the strength, direction and distribution of trophic interaction modifications within food webs influence community stability (Arditi et al, 2005;Terry et al, 2020) and ecosystem function (Goudard & Loreau, 2008). However, we know little about how trophic interaction modifications vary in strength and direction among many diverse potential modifier species in natural communities (Terry et al, 2020;Wootton & Emmerson, 2005). This limits our understanding of when trophic interaction modifications should be included in predictive models of population dynamics, and of the role of trophic interaction modifications in structuring communities more generally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such work is both laborious and often imprecise, even for the links within a subset of a food web [ 4 ]. Additionally, some elements, such as non-consumptive interactions among multiple predators, cannot be understood solely from a pairwise predator-prey perspective because the presence of a third species modifies the interaction [ 5 ]. Although dynamic food-webs can accurately describe observed interactions, their complexity has made it unwieldy to map the abundance dynamics of diverse predator-prey assemblages in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms include avoidance of intraguild predation and interference among predator species as well as facilitation [ 22 , 26 29 ]. Such interactions are not described by the original ATN model, and so the model poorly captures their population-level effects [ 5 , 17 ]. Jonsson et al [ 17 ]’s results, that increasing trophic complexity weakened the ability of their model to explain the data, strongly suggested that it is a lack of behavior-based non-consumptive interspecific interference effects in the ATN model that is the main cause for its inability to accurately predict trophic interaction strength in more complex webs.…”
Section: Introductionmentioning
confidence: 99%